Mitigation of Greenhouse Gas Emissions by Optimizing Groundwater Level in Boreal Cultivated Peatland - Heikkinen, Jaakko; Lång, Kristiina; Honkanen, Henri; Myllys, Merja (Springer Nature, 2024)
Optimizing the level of groundwater presents a viable strategy for mitigating the greenhouse gas (GHG) emissions associated with the cultivation of peatlands. This study investigated the impact of soil hydrological conditions on carbon dioxide (CO2) and methane (CH4) emissions. The CO2 and CH4 emissions from bare soil were continuously measured using an automated chamber system throughout the growing seasons from 2021 to 2023 at a boreal cultivated peat soil site. Annual CO2 emissions from soil respiration averaged to 21,600 kg ha-1 (April-November) corresponding to carbon (C) loss of 5890 kg ha-1. The CO2 emissions were highly temperature dependent. Lowering the groundwater level (GWL) was found to increase the CO2 emissions nearly linearly. The soil functioned as a CH4 sink for the majority of the growing season, and the total sink corresponded to 27 and 20 kg ha-1 yr-1 CO2 equivalent in 2022 and 2023, respectively. The CH4 emissions occurred generally when soil water content (SWC) exceeded 0.6 m3 m-3 and when GWL was at the depth of less than 30 cm from soil surface. For optimal climate efficiency the mitigation measures must be implemented during the mid-growing season, and the water table should be brought close to the soil surface. Potentially, this can hamper the operation of machinery on the field and reduce the harvested yield. Thus, comprehensive cost-benefit analysis is necessary before adopting a raised water table level in large-scale crop production.
Keywords: peatland cultivation; soil hydrological conditions; GHG fluxes; climate impact; controlled drainage